Least limiting water range in Oxisols under different levels of machine traffic - De Vares Rossetti, Karina [UNESP] (2017)
This work aimed, to evaluate the structural behavior of Oxisols based on the least limiting water range (LLWR) and establish relations with corn crop. The experiment was carried out in a randomized block design with five treatments and four replications. Soil samples collected at the layer of 0-0.20 m depth in a Haplustox (LVd) and an Eutrustox (LVef) were used. The compaction treatments consisted of T0= no additional compaction; T1 and T2= two and four passes with a 4 t tractor, respectively; T3 and T4 = two and four passes with a 10 t tractor, respectively. The range of LLWR variation in the LVd was the lowest one and varied from 0.01 to 0.04 m3 m-3, whereas in the LVef varied from 0.03 to 0.13 m3 m-3 for the critical soil penetration resistance (PRc) of 2 MPa. It was observed that critical bulk density (BDc) values were 1.76 and 1.40 Mg m-3 in the LVd and the LVef, respectively. The highest frequency of bulk density (BC ≥ BDc) occurred from the T1 to T4 (LVd) and from the T2 to T4, however, a reduction in corn yield was not observed. The determination of the LLWR was efficient and complementary for identifying more favorable or more impeditive conditions to compaction in the LVef for the corn crop development in relation to the LVd.